Faktor Penyebab yang Paling Dominan Kejadian Dermatitis Kontak Iritan pada Pekerja di TPA (Tempat Pemrosesan Akhir) Talang Gulo Kota Jambi - Mawaddah, Rakhmi Aisyah El; Fairuz, Fairuz; Kalsum, Ummi (Universitas Batanghari Jambi, 2024)
This study aims to analyze the dominant causal factors of subjective complaints of irritant contact dermatitis in workers at the Talang Gulo Landfill in Jambi City. The data analysis method in this study explains the stages of analysis, namely starting with data collection, data processing and data analysis. Data collection was carried out by the researcher himself and assisted by three enumerators and the head of waste management at the Talang Gulo Landfill. The data that has been obtained is then collected, processed according to the objectives and conceptual framework of the study. After the data is collected, data processing is carried out. Data processing is carried out through the stages of editing, coding, data entry, and data cleaning. The data that has been processed is then analyzed using univariate analysis, bivariate analysis and multivariate analysis. The results of the study showed that the factors related to subjective complaints of irritant contact dermatitis are knowledge, chemical exposure from waste and personal hygiene. Of the three factors, personal hygiene is the most dominant factor in the occurrence of subjective complaints of irritant contact dermatitis. Respondents who have poor personal hygiene have a 6.123 times higher risk of experiencing subjective complaints of irritant contact dermatitis when compared to respondents who have good personal hygiene after being controlled with the variables of knowledge and chemical exposure from waste.